ChemInform Abstract: Direct Pd‐Catalyzed Cross‐Coupling of Functionalized Organoaluminum Reagents. Issue 14 (20th March 2013) - Groll, Klaus; Bluemke, Tobias D.; Unsinn, Andreas; Haas, Diana; Knochel, Paul
Abstract A broad spectrum of aromatic or benzylic aluminum reagents, generated in situ from different types of substrates is demonstrated to give the expected products.